Changing Results to Change Results: Nudging Antimicrobial Prescribing for Clostridium difficile. (16th December 2020) - Herman, Dakoda J; Sarabia, Alicia; Chan, Helen; Graham, Christopher
Abstract: Background: Patients who test positive for Clostridium difficile by polymerase chain reaction (PCR), with a negative toxin enzyme immunoassay (EIA), are commonly colonized and do not require treatment. However, clinicians often treat based on a positive PCR result regardless of the toxin EIA result. We evaluated the clinical impact of a microbiology reporting nudge, changing from a report that included both assay results along with treatment recommendations to one that suggested clinicians consider C difficile colonization or early infection. Methods: We conducted a retrospective cohort study of all adult patients admitted to a large multisite community hospital with a positive C difficile PCR result and negative toxin EIA from January 1, 2016 to June 30, 2018. We examined total days of therapy (DOT) and impacts on clinical outcomes. Results: One hundred ninety-nine episodes occurred preintervention and 165 episodes occurred postintervention. The mean DOTs per episode decreased from 13.6 to 7.9 days (difference −5.8 days; 95% confidence interval, −3.9 to −7.6) postintervention, with statistical process control charts suggesting special cause variation. Patients receiving no treatment increased from 6.5% to 23.6% postintervention ( P < .0001). No significant changes in subsequent toxin positive disease (9.0% vs 6.7%), colectomy (0% vs 0.6%), mortality (7.5% vs 12.1%), or length of stay (18.5 vs 16 days) were observed. Conclusions: Microbiology reporting nudges raising the possibility of C difficile colonization were associated with altered prescribing, reinforcing a postanalytic strategy for invoking change. Decreases in antimicrobial prescribing occurred without increasing subsequent disease or other adverse outcomes, suggesting a safe strategy for decreasing unnecessary treatment of C difficile colonization.